Multi-period Financial Feasibility Model for Collective Sale of Multiple-owner Residential Developments in Singapore - Tan, Hong Boon (2006)
Practitioners of real estate investment analysis in Singapore are familiar with the use of both the conventional residual valuation (RV) method and the discounted cash flow (DCF) analysis in their evaluations of development projects. However, RV method is more commonly use in land price estimation for local projects mainly due to the relatively short investment horizon of typical development period of only two to three years for most projects, i.e. DCF analysis seemingly become unnecessary.